2020
DOI: 10.1177/0361198120924630
|View full text |Cite
|
Sign up to set email alerts
|

How Built Environment Impacts Online Car-Hailing Ridership

Abstract: Extensive research has shown that unilateral optimization of transit systems is not effective enough to significantly increase its transport efficiency. Considering that urban land-use characteristics, including residential, work, consumption, transit, and so forth, are significantly interrelated with travel demands and travel behaviors, this paper provides a way to optimize transit system by raising awareness of the relation between ridership and built environment. This paper adopted point of interest (POI) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
1
21
1
Order By: Relevance
“…One limitation of this research is that it only considers built environment variables. Although the legitimacy of variable selection mirrors that of previous studies (Bi et al, 2020;Ma et al, 2018), incorporating other finescale demographic and policy factors might improve model performance and provide further practical planning guidance. In addition, although factors that influence personal choices on bus and taxi are beyond the scope of this study, it is worth investigating this aspect and further unravelling complicated interactions between bus and taxi ridership.…”
Section: Ack N Owled G M Entsmentioning
confidence: 89%
See 1 more Smart Citation
“…One limitation of this research is that it only considers built environment variables. Although the legitimacy of variable selection mirrors that of previous studies (Bi et al, 2020;Ma et al, 2018), incorporating other finescale demographic and policy factors might improve model performance and provide further practical planning guidance. In addition, although factors that influence personal choices on bus and taxi are beyond the scope of this study, it is worth investigating this aspect and further unravelling complicated interactions between bus and taxi ridership.…”
Section: Ack N Owled G M Entsmentioning
confidence: 89%
“…Previous studies have indicated that bus stations are often located in areas where people are densely distributed and that the built environment around a bus station is often relatively homogeneous. Therefore, bus stop‐based Thiessen polygons are appropriate spatial analysis units for travel behavior studies (Bi et al., 2020). Bus stations located within 500 m were first aggregated to avoid potential biases that might be propagated to the analysis from the following two aspects.…”
Section: Study Region and Datamentioning
confidence: 99%
“…Connection from the metro station to the trip destination is required, which is the critical component of a multimodal journey; it is traditionally achieved by combining other travel modes, like walking, cycling, and the use of bus and taxi ( 10 , 20 ). Benefitting from the rapid development of internet technology and mobile payment, many cities witnessed the explosive growth in emerging transport services in recent years, including bike-sharing and ridesourcing programs ( 21 , 22 ). Besides being a stand-alone travel mode, they have another essential function: serving as the feeder mode to the metro.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ridesourcing schemes are another typical example of a sharing economy service pertaining to transportation ( 21 , 28 , 29 ). Prearranged and on-demand ride services that match drivers and passengers using smartphone applications have rapidly spread worldwide because of their convenience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Xiao et al found that Shanghai presents a two-level hierarchical polycentric urban structure feature by applying a spatial embedded network model [40]. To build the original destination (OD) matrix, the common types of traffic analysis unit, include regular grids [41][42][43][44][45], hexagons [46], and irregular polygons (usually obtained by dividing the road network or district boundary). In particular, the regular grid is the most common due to its advantages, such as ease of use and visualization.…”
Section: Introductionmentioning
confidence: 99%